Empagliflozin treatment differentially modifies visceral and subcutaneous adipose tissue lipidomes and pro-inflammatory cytokines in zucker fatty diabetic rats. (3rd October 2022) - Morana-Fernandez, S; Aragon-Herrera, A; Otero-Santiago, M; Anido-Varela, L; Tarazon, E; Portoles, M; Rosello-Lleti, E; Comella, F; Gonzalez-Juanatey, J R; Feijoo-Bandin, S; Lago, F
Abstract:  : EMPA-REG OUTCOME (Empagliflozin, Cardiovascular Outcome Event Trial) trial highlighted the relevance of pharmacological inhibition of sodium-glucose cotransporter 2 (SGLT2) for the treatment of patients with type 2 diabetes mellitus (T2DM) and/or cardiovascular disease. Although the pathways through which SGLT2 inhibitors exert a beneficial effect on the cardiovascular system are still unknown, it has been suggested that energy metabolism regulation and a reduction of systemic inflammation could be some of the mechanisms implicated. Available data also suggests that empagliflozin treatment could be able to exert regulatory effects on adipose tissue (AT) depots. The aim of our study was to evaluate the impact of empagliflozin treatment on the lipidome of visceral (VAT) and subcutaneous adipose tissue (SAT) depots in a rat model of obesity and T2DM. Diabetic obese Zucker Fatty (ZDF) rats were treated with 30 mg/kg/day of empagliflozin p.o for 6 weeks. The lipidomes of VAT and SAT depots were analyzed using ultra-high performance liquid chromatography coupled to mass spectrometry. Empagliflozin's effect on pro-inflammatory markers in AT was analyzed by RT-PCR. In VAT, 18 metabolites were significantly altered in empagliflozin-treated rats vs. controls. Nearly all diglycerides tested (13 of 14) were significantly increased in treated rats, as the most notable altered chemical class. Furthermore, 3 oxidized fatty acids (FA) and FA like gadoleic acid and linoleic acid were also significantly increased. In SAT, a total of 14 metabolites were significantly altered. Most of them (13 of 14) were glycerophospholipids. Significantly lower levels of 4 lysophosphatidylethanolamines, 4 lysophosphatidylcholines, and 3 lysophosphatidylinositols and higher levels of 2 phosphatidylcholines were shown. In contrast to VAT, a significant decrease in most of these metabolites was observed in empagliflozin-treated samples. Several ratios of metabolites were also calculated to infer the potential enzyme activities related to lipid metabolism in both VAT and SAT. However, the ratios studied were only statistically significant in VAT of empagliflozin-treated rats vs. control, where the main potential enzyme activities altered were desaturases and elongases. Empagliflozin treatment also reduces the expression of the pro-inflammatory cytokines interleukin-1 beta (IL-1β), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNFα) and monocyte-chemotactic protein-1 (MCP-1) in VAT, with no changes in SAT, except for interleukin-13 (IL-13), which also decreases compared to untreated diabetic ZDF rats. In conclusion, empagliflozin increased oxidized FA and diglycerides in VAT and decreased glycerophospholipid levels in SAT. The anti-inflammatory effect of empagliflozin in VAT is not observed in SAT. The effect of empagliflozin on the regulation of the adipose tissue lipidome and inflammatory profile is different depending on the localization of the depots. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Boehringer Ingelheim Pharma GmbH and Co